Marketing Strategies to Support the Effectiveness of Revolving Alms Philanthropic Institution Fundraising - Uki Masduki; Diana Yusuf; Arif Budimanta; Iwan Setiadi (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2026)
Introduction: Revolving alms is a model of economic empowerment in which funds collected from the community are channeled to beneficiaries in the form of productive loans, not just consumptive loans. To support this concept, an effective marketing strategy is needed, especially through digital marketing, the use of social media, diversification of fundraising methods, and transparency in fund management. Research Methods: This study uses a literature review method by analyzing articles and journals related to the marketing of philanthropic institutions during the last 10 years, especially the last 10 years. Results: The results show that digital marketing and social media are the most effective strategies to expand community reach, increase transparency, and speed up the fundraising process. A combination of traditional and modern approaches such as direct visits, crowdfunding, and collaboration with companies through CSR programs can maximize the impact of rolling alms. Conclusion: This study demonstrates that digital marketing and the use of social media significantly enhance the effectiveness of revolving alms fundraising by expanding outreach, increasing donor participation, and improving operational efficiency. Fundraising diversification and transparent fund management are essential in building public trust and ensuring program sustainability. Therefore, optimizing digital platforms and strengthening transparency are key strategies for sustainable revolving alms institutions.